Bone Regeneration in rat using a gelatin/bioactive glass nanocomposite scaffold along with endothelial cells (HUVECs). Issue 6 (27th April 2018) - Kazemi, Mansure; Azami, Mahmoud; Johari, Behrooz; Ahmadzadehzarajabad, Maryam; Nazari, Bahareh; Kargozar, Saeid; Hajighasemlou, Saieh; Mozafari, Masoud; Soleimani, Mansooreh; Samadikuchaksaraei, Ali; Farajollahi, Mohammad
Abstract: In our previous study, a three‐dimensional gelatin/bioactive glass nanocomposite scaffold with a total porosity of about 85% and pore sizes ranging from 200 to 500 μm was prepared through layer solvent casting combined with lamination technique. The aim of this study was to evaluate in vitro biocompatibility and in vivo bone regeneration potential of these scaffolds with and without endothelial cells when implanted into a critical‐sized rat calvarial defect. MTT assay, SEM observation, and DAPI staining were used to evaluate cell viability and adhesion in macroporous scaffolds and results demonstrated that the scaffolds were biocompatible enough to support cell attachment and proliferation. To investigate the in vivo osteogenesis of the scaffold, blank scaffolds and endothelial/scaffold constructs were implanted in critical‐sized defects, whereas in control group defects were left untreated. Bone regeneration and vascularization were evaluated at 1, 4, and 12 weeks postsurgery by histological, immunohistochemical, and histomorphometric analysis. It was shown that both groups facilitated bone growth into the defect area but improved bone regeneration was seen with the incorporation of endothelial cells. The data showed that the porous Gel/BaG nanocomposite scaffolds could well support new bone formation, indicating that the proposed strategy is a promising alternative for tissue‐engineered bone defects.